-7x-(10-x)=-58

Simplify each term.

Apply the distributive property.

-7x-1⋅10–x=-58

Multiply -1 by 10.

-7x-10–x=-58

Multiply –x.

Multiply -1 by -1.

-7x-10+1x=-58

Multiply x by 1.

-7x-10+x=-58

-7x-10+x=-58

-7x-10+x=-58

Add -7x and x.

-6x-10=-58

-6x-10=-58

Add 10 to both sides of the equation.

-6x=-58+10

Add -58 and 10.

-6x=-48

-6x=-48

Divide each term in -6x=-48 by -6.

-6x-6=-48-6

Cancel the common factor of -6.

Cancel the common factor.

-6x-6=-48-6

Divide x by 1.

x=-48-6

x=-48-6

Divide -48 by -6.

x=8

x=8

Solve for x -7x-(10-x)=-58